Strategic Entrepreneurship: A Review and Research Agenda - Ireland, R. Duane; Withers, Michael C.; Harrison, Joseph S.; Boss, David S.; Scoresby, Richard (Entrepreneurship Theory and Practice, 2023)
Strategic entrepreneurship integrates the fields of strategy and entrepreneurship to consider firms’ simultaneous engagement in opportunity- and advantage-seeking behaviors to create wealth. Since its conceptualization in the early 2000s, the study of SE has gained considerable momentum. At the same time, some scholars criticize SE and question its comprehensiveness as a way to understand the strategic application of entrepreneurship. We present a comprehensive review and integration of research related to the study of SE as a construct, theoretical model, and research domain. In doing this, we offer a research agenda across these different approaches to the study of SE.